Fiscal Capacity, Civil Service Quality, and Community Welfare Mediation and Moderation Analysis - Iskandar Sam; Haryadi; Sri Rahayu; Wirmie Eka Putra; Ratih Kusumastuti (The Indonesian Accounting Review, 2026)
This study investigates the influence of regional financial conditions and the status of the State Civil Apparatus (ASN) on community welfare, with government performance as a mediating variable and local government size as a moderating variable. A quantitative approach is employed, utilizing secondary data from district and city governments in Jambi Province, and the analysis is conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with WarpPLS 8.0. The results demonstrate that regional financial conditions exert a significantly negative effect on government performance, whereas ASN conditions have a significantly positive effect. Both regional financial conditions and ASN status significantly enhance community welfare, whereas government performance has a significantly negative impact on welfare. Furthermore, government performance does not mediate the relationship between regional financial conditions and ASN status and community welfare. Local government size moderates the effect of regional financial conditions on government performance but does not moderate the effect of ASN status. These findings indicate that community welfare is more directly influenced by regional financial conditions and civil servants' status than by government performance.